Analysis Of 5C Principles In Bank To Minimize The Occurrence Of Credit Contracts - Sinaga, Juli Kristabel; Br Ginting, Elrisa Marsanda; Girsang, Fani Magdalena; Hasyim (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This research discusses the importance of analyzing the 5C principles in managing bank credit to minimize the risk of non-performing loans. The research method used is a qualitative approach with descriptive analysis and a library research approach. The research results show that banks need to consider the character, capacity, capital, collateral and condition of prospective debtors before providing credit to minimize the risk of credit congestion. These factors, known as the 5C principles, help banks assess credit provision and minimize the risk of non-performing loans. Research also highlights the role of character, capacity, collateral, capital and economic conditions in assessing credit provision. The 5C principles are used as a guide for credit analysts in banking institutions to ensure credit is provided with minimal risk. Thus, this research provides comprehensive insight inukughgyto the importance of the 5C principles in bank credit management to minimize the risk of non-performing loans